Altered interaction of physiological activity and behavior affects risky decision-making in ADHD - Halbe, Eva; Kolf, Fabian; Heger, Alina Sophie; Hüpen, Philippa; Bergmann, Moritz; Aslan, Behrem; Harrison, Ben J.; Davey, Christopher G.; Philipsen, Alexandra; Lux, Silke (Frontiers in Human Neuroscience, 2023)
Background: Adult ADHD is often associated with risky decision-making behavior. However, current research studies are often limited by the ability to adequately reflect daily behavior in a laboratory setting. Over the lifespan impairments in cognitive functions appear to improve, whereas affective functions become more severe. We assume that risk behavior in ADHD arises predominantly from deficits in affective processes. This study will therefore aim to investigate whether a dysfunction in affective pathways causes an abnormal risky DM behavior in adult ADHD Methods: Twenty-eight participants with ADHD and twenty-eight healthy controls completed a battery of questionnaires regarding clinical symptoms, self-assessment of behavior and emotional competence. Furthermore, skin conductance responses were measured during the performance in a modified version of the Balloon Analogue Risk Task. A linear mixed-effects model analysis was used to analyze emotional arousal prior to a decision and after feedback display. Results: Results showed higher emotional arousal in ADHD participants before decision-making (ß=-0.12, SE=0.05, t=-2.63, p<0.001) and after feedback display (ß=-0.14, SE=0.05, t=-2.66, p=0.008). Although risky behavior was greater in HC than in ADHD, we found a significant interaction effect of group and anticipatory skin conductance responses regarding the response behavior (ß=107.17, SE=41.91, t=2.56, p=0.011). Post-hoc analyses revealed a positive correlation between anticipatory skin conductance responses and reaction time in HC, whereas this correlation was negative in ADHD. Self-assessment results were in line with the objective measurements. Conclusion: We found altered changes in physiological activity during a risky decision-making task. The results confirm the assumption of an aberrant relationship between bodily response and risky behavior in adult ADHD. However, further research is needed with respect to age and gender when considering physiological activities.